(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Globalization is a key factor influencing various aspects of human life, particularly the education sector. This article explores the effects of globalization on the education system, highlighting the opportunities it creates, such as the adoption of global standards, technological advancements, and increased academic mobility. However, it also addresses the challenges posed by globalization, including the risk of homogenization of educational content and unequal access to resources. Additionally, the article emphasizes the importance of preserving national identity while embracing globalization. Recommendations for balancing the benefits and drawbacks of globalization in education are also provided.